Synergies and Value Creation : The Perspective of Participants in Mergers and Acquisitions - Suleymanova, Zarina (2014)
Synergies have always been viewed as the most important driver for majority of Mergers and Acquisitions (M&As). An array of synergetic wonders is attributable to their successful realisation. Some synergies are traditional and predictable in economic terms, while there are those requiring a unique value creating approach. Business reality is represented with abundance of particularities, complexities and idiosyncrasies. Screening, appreciating and validating the deal sensitive assumptions is what distinguishes the successful ones. The elimination of uncertainty is what facilitates to creation of wealth. A practical view of participants in M&As has been sought to comprehend synergies’ life cycle from the deal inception until potential contribution to stakeholders’ value maximisation. Although, participants in M&As view synergetic pursuits as the driving force for majority of transactions, their opinion on value creative aspect of synergies is divided. The opinion split is due to either inability to realise and assess the benefits shortly after a transaction’s completion or due to ambiguity in ascertainment the value beneficiaries between acquiring and target shareholders. Remarkably, top executives are the avid supporters, while investment bankers exhibit a neutral stand on value creation from the synergies in M&As. Competitive advantage and growth through revenue gains are the leading synergetic aspirations aiming shareholder value enhancement. Poorly managed and undervalued companies have been indicated to be the focus of empire building acquirers. Lack of meticulously structured integration strategy comprehending both tangible and intangible factors is the main cause for M&A failure according to majority of respondents. Potential “extraordinary” synergetic benefits are the main incentive to merge and acquire for most of respondents. Effective and efficient allocation of resources in growth maximisation is what expected from a combination of operational and financial synergies. New markets’ penetration by means of either brand reinforcement or customer base increase is a predominantly sought result from operational synergies. Financial synergetic effect is mostly translated into share value increase. Another interesting alignment is the opportunity to participate in governmental projects with cost-effective collaboration. The reduction of costs is attempted by means of increased level of capacity utilisation and purchase price reduction. Sustainable synergies’ pursuit has been discovered as a latent factor. Success of synergetic realisation is seen through synergy evaluation on every stage of merger, advance planning of integration, comprehensive due diligence and acquirer’s superior management skills. Accounting method prevails in most respondents’ answers, as the leading approach of evaluation on pre- and post-merger stages. Participants believe that acquisition premium payment is directly correlated with expected synergy and excessive premiums are traced back to its valuation. CEO overconfidence and excitement of trading are the main causes of subjectivism in excessive premiums. An equation of value of synergy with acquisition premium is considered to benefit target shareholders by more than half of respondents, except for disagreeing investment bankers.